2017
DOI: 10.3390/gels3040039
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Based Physical Gels Endowed with Thixotropic Behaviour

Abstract: Thixotropy is one of the oldest documented rheological phenomenon in colloid science and may be defined as an increase of viscosity in a state of rest and a decrease of viscosity when submitted to a constant shearing stress. This behavior has been exploited in recent years to prepare injectable hydrogels for application in drug delivery systems. Thixotropic hydrogels may be profitably used in the field of regenerative medicine, which promotes tissue healing after injuries and diseases, as the molten hydrogel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…The comparison between the two classes of collagen mimetic peptides having same composition but different domain arrangements showed that the larger nucleation domains resulted in rapid fiber formation and gelation while short nucleation domains left the peptide soluble for longer period (Sarkar et al, 2014). The thixotropic supramolecular hydrogels formed in response to external environmental stimuli have wide ranges of potential biological applications (Levin et al, 2014;Seow and Hauser, 2014;Loic, 2017;Zanna and Tomasini, 2017;Mondal et al, 2020). The stability of peptide-based hydrogels, specially to enzymatic degradation has been reviewed by Yadav et al (2020).…”
Section: Applications Of Peptide Self-assembliesmentioning
confidence: 99%
“…The comparison between the two classes of collagen mimetic peptides having same composition but different domain arrangements showed that the larger nucleation domains resulted in rapid fiber formation and gelation while short nucleation domains left the peptide soluble for longer period (Sarkar et al, 2014). The thixotropic supramolecular hydrogels formed in response to external environmental stimuli have wide ranges of potential biological applications (Levin et al, 2014;Seow and Hauser, 2014;Loic, 2017;Zanna and Tomasini, 2017;Mondal et al, 2020). The stability of peptide-based hydrogels, specially to enzymatic degradation has been reviewed by Yadav et al (2020).…”
Section: Applications Of Peptide Self-assembliesmentioning
confidence: 99%
“…This property is particularly important for soft materials useful for biomedical applications. 25 Thermal analysis…”
Section: Rheological Evaluationmentioning
confidence: 99%
“…The thixotropy of peptide-based hydrogel, especially those formed by short peptides, originated from non-covalent interactions as the main driving force in their self-assembly process, containing hydrogen bonding, π–π stacking, electrostatic effects, and hydrophobic interactions, etc ( Yadav et al, 2020 ). These effects tend to be weak and vulnerable to shear stress and show dynamic changes accompanied by variation in shear force ( Zanna and Tomasini, 2017 ). Shear force is input in this hydrogel system as external energy, making the system no longer thermodynamically isolated, and distance-dependent intermolecular interactions deviate from the chemical equilibrium state, which ultimately leads to a state comparable to infinite dilution with no likelihood of rebinding.…”
Section: Introductionmentioning
confidence: 99%